Bubble‐Sheet‐Like Interface Design with an Ultrastable Solid Electrolyte Layer for High‐Performance Dual‐Ion Batteries. Issue 17 (22nd February 2017) - Qin, Panpan; Wang, Meng; Li, Na; Zhu, Haili; Ding, Xuan; Tang, Yongbing
Abstract : In this work, a bubble‐sheet‐like hollow interface design on Al foil anode to improve the cycling stability and rate performance of aluminum anode based dual‐ion battery is reported, in which, a carbon‐coated hollow aluminum anode is used as both anode materials and current collector. This anode structure can guide the alloying position inside the hollow nanospheres, and also confine the alloy sizes within the hollow nanospheres, resulting in significantly restricted volumetric expansion and ultrastable solid electrolyte interface (SEI). As a result, the battery demonstrates an excellent long‐term cycling stability within 1500 cycles with ≈99% capacity retention at 2 C. Moreover, this cell displays an energy density of 169 Wh kg −1 even at high power density of 2113 W kg −1 (10 C, charge and discharge within 6 min), which is much higher than most of conventional lithium ion batteries. The interfacial engineering strategy shown in this work to stabilize SEI layer and control the alloy forming position could be generalized to promote the research development of metal anodes based battery systems. Abstract : A bubble‐sheet‐like aluminum foil is developed and used as anode material and current collector in a dual‐ion battery (DIB) . This novel structure helps guide the AlLi alloying position within the hollow nanospheres and confines the alloy sizes. As a result, this design significantly relieves the volumetric change, and thus maintains ultrastable solid–electrolyte layer during repeated battery reactions. The fabricated DIB demonstrates excellent long‐term cycling stability.